DINAMIKA KEBIJAKAN MONETER DALAM MENGENDALIKAN INFLASI DAN MENDORONG PERTUMBUHAN EKONOMI - Abd. Rosit, Siva Indana Arisanti; Baharudin Rachman; Rini Puji Astuti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the dynamics of monetary policy in controlling inflation and promoting economic growth in Indonesia. The research problem focuses on assessing the effectiveness of monetary policy instruments such as benchmark interest rates, reserve requirements, and open market operations in achieving price stability while encouraging national economic growth. A qualitative literature review method was employed, combining findings from previous studies, official reports from Bank Indonesia, and relevant secondary data. The results indicate that the implementation of monetary policy, particularly through the inflation targeting framework and innovations such as the BI 7-Day Reverse Repo Rate, has contributed to reducing inflation and maintaining sustainable economic growth. Furthermore, the synergy between monetary policy and fiscal policy has strengthened Indonesia’s macroeconomic stability. The study concludes that the effectiveness of monetary policy depends on the accuracy of instruments, the credibility of the monetary authority, and the coordination across policies to address both domestic and global economic dynamics.